Uma análise de conteúdo escrito sobre as referências à responsabilidade social corporativa em instituições de ensino superior no Rio de Janeiro - Moreira, Bruno Siqueira (2015)
Considering the importance of corporate social responsibility contents for the contemporary society and corporations, this research aimed at observing with further details the official documents published by universities and higher education institutions which references were being made to corporate social responsibility, as defined by Elkington (1997), and the kind of education being offered by the undergrad business administration courses in the city of Rio de Janeiro. This research is based on content analysis of documents published in the world wide web by the undergrad courses, followed by a reflection through the theories of curriculum matrixes, aspects of sociology of professions and the possibility of a 'hidden' curriculum grid. We conclude that there is evidence of little focus dedicated to CSR-related contents in undergraduate courses, as well as a small percentage of time exclusively dedicated to these topics. Nonetheless, considering that curricula can be related to the maintenance of power and silencing of emerging contents for the maintenance of hegemonic interests, we note that we cannot find out whether CSR-related contents are being taught across the board through a 'hidden' curriculum as we have done a research based on content analysis of written documents. Thus, we leave an open possibility of further research to investigate this possibility.